Cost-effectiveness of primary endocrine therapy comparing against surgery as the initial treatment strategy in older women with primary breast cancer - Mousa, Rimal (2017)
Background Breast cancer is highly prevalent in older women. Although surgery is the main initial treatment for younger population, research has demonstrated that older women with primary breast cancer have different tumour biology, comorbidities, and patient preferences from younger patients, and hence may benefit from primary endocrine therapy (PETx), such as Tamoxifen and aromatase inhibitors (AIs). However, there is no cost-effectiveness study that compares the use of different treatment strategies in older women.